Trends in monetary policy transparency - Petra Maria Geraats (Center for Economic Studies and ifo Institute (CESifo), 2009)
Transparency has become a prominent feature of monetary policy. This paper provides an overview of central bank communication practices and is the first to systematically analyze transparency trends throughout the world and across monetary policy frameworks. It shows that increases in information disclosure have not been confined to inflation targeting but extend to other monetary policy frameworks, although there are significant differences. In addition, countries with higher inflation and economic development have undergone larger increases in transparency. Moreover, it shows that greater transparency has been followed by lower average inflation.
Keywords: E42; E58; 330; Transparency; monetary policy; central bank communication; monetary policy frameworks; Geldpolitik; Staatliche Information; Zentralbank; Informationsverhalten; Welt